Chronology of the western world, 1000-1500 AD - Society for Visual Education (Chicago, Ill. The Society, 1988)
Examines Western Europe and the rise of the middle class, and the growing conflicts between church and state.
VHS.
Keywords: World history -- 1000-1500 A.D.; Europe -- History -- 476-1492.; Europe -- History -- 476-1492.